2017
DOI: 10.1097/md.0000000000009083
|View full text |Cite
|
Sign up to set email alerts
|

Locked plating as an external fixator in treating tibial fractures

Abstract: Objectives:This article is a systematic review of the published literature about the biomechanics, functional outcomes, and complications of a locked plate as an external fixator in treating tibial fractures.Methods:We searched the PubMed, Ovid Medline, Embase, ScienceDirect, and Cochrane Library databases to retrieve the relevant studies. Studies published in English and Chinese which assessed adult patients and more than 4 cases who had sustained any type of fresh tibial fracture treated with the external lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
(80 reference statements)
1
33
0
Order By: Relevance
“…Traditionally, external fixators have been selected as osteosynthesis devices for the treatment of open tibial fractures and certain closed tibial fractures with severe injury to soft tissue [1,2]. External fixation devices provide a promising and satisfactory alternative for better soft tissue care and for preserving periosteal perfusion to the regions of fracture [3,4]. They can also be selected for use as interim or definite devices of fracture fixation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, external fixators have been selected as osteosynthesis devices for the treatment of open tibial fractures and certain closed tibial fractures with severe injury to soft tissue [1,2]. External fixation devices provide a promising and satisfactory alternative for better soft tissue care and for preserving periosteal perfusion to the regions of fracture [3,4]. They can also be selected for use as interim or definite devices of fracture fixation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of axial and torsional stiffness of externalized LCP and standard unilateral external fixator was studied by the Ang B H, Chen J Y et al and they found that mean axial stiffness was comparable between two and torsional stiffness was statistically higher in externalized LCP than standard unilateral external fixator [23]. Systematic review of literature on supracutaneous plating also concluded that though internal fixation by LCP is stronger than externalized LCP but there was no significant difference between externalized LCP and traditional external fixator in terms of biomechanics [7,24].…”
Section: Original Research Articlementioning
confidence: 99%
“…Hence the evolution of surgical techniques was to stabilize these fractures with minimal invasiveness to maintain the biology of soft tissue and bone [4,5]. Tibial diaphyseal fractures could easily be treated with closed interlocking nails but metaphyseal areas at both ends had surgical dilemma in choosing the implant and technique so as not to violate already traumatized soft tissue [6,7]. MIPO technique and low profile anatomical locking compression plating reduced the risk of skin breakage and infection to some extent with promising results [8].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, external fixators have been selected to be osteosynthesis devices in the treatment of open tibial fractures and certain closed tibial fractures with severe injury of soft tissue [1,2]. External fixation devices provide a promising and satisfactory alternative for better soft tissue care and preserving periosteal perfusion to the regions of fracture [2,3]. They can be a choice for interim or definite device of fracture fixation [4].…”
Section: Introductionmentioning
confidence: 99%